2008
DOI: 10.1590/s0066-782x2008000200009
|View full text |Cite
|
Sign up to set email alerts
|

Acesso à internação e fatores associados ao óbito hospitalar por doenças isquêmicas do coração no SUS

Abstract: SummaryBackground: Analyses on mortality rate due to diseases when outcome depends on proper, timely medical intervention may point out the vulnerabilities and inequity associated to health care access. Ischemic heart diseases will act as models for such assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 28 publications
0
7
0
4
Order By: Relevance
“…1 Other studies have found associations between age and hospital death. 5,7,17,22 It was observed that males presented a greater chance of death than did females; an association between sex and hospital mortality has already been described in the literature. 1,5,18 On the other hand, in an analysis on myocardial revascularization surgery, Noronha et al 5 (2003) found a greater likelihood of death among women.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…1 Other studies have found associations between age and hospital death. 5,7,17,22 It was observed that males presented a greater chance of death than did females; an association between sex and hospital mortality has already been described in the literature. 1,5,18 On the other hand, in an analysis on myocardial revascularization surgery, Noronha et al 5 (2003) found a greater likelihood of death among women.…”
Section: Discussionmentioning
confidence: 77%
“…This model can be used to predict hospital deaths and is in accordance with other proposals in the literature that also used logistic regression models to predict hospital deaths according to patients' profi les. 1,7,17 The fi nal model presented good predictive performance, with an area under the ROC curve of 0.781, and it is proposed that this should be a general index. Other studies have been conducted in relation to specifi c diagnoses, using variables from the HIS-SUS database to predict hospital deaths.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Para cada dia a mais de internação no hospital e na UTI, o modelo final estimou incrementos na chance de morte hospitalar de 1,0 e de 4,0%, respectivamente. Diversos autores, entre eles Noronha e colaboradores, 6 Evangelista e colaboradores, 13 Gomes e colaboradores 4 e Dias e colaboradores, 14 também encontraram associação positiva entre TMH e uso de UTI. Trata-se de resultados esperados, uma vez que pacientes mais graves necessitam de tecnologias mais complexas, demandando maior tempo de internação hospitalar e uso mais prolongado de UTI, além do que, por sua condição de base (anterior), possuem maior probabilidade de morte durante o período de internação.…”
Section: Discussionunclassified
“…Essas observações discordam daquelas obtidas por Gomes e colaboradores, 4 que encontraram taxa de mortalidade superior nos hospitais da rede pública (7,19%) quando comparada à TMH em comparação com os hospitais privados (6,04%), em atendimentos SUS no Rio Grande do Sul (OR ajustado=1,6). Da mesma forma, Evangelista e colaboradores, 13 ao es- 4 sobre o Rio Grande do Sul. No DF, observou-se maior chance de óbitos nos hospitais de médio porte (8,0%), seguidos dos de grande porte (3,8%) e de pequeno porte (0,0%).…”
Section: Discussionunclassified